Orientação sexual na escola: a concepção dos professores de Jandira - SP - Jardim, Dulcilene Pereira (2006)
School has an important role in sexual orientation during adolescence. This study aimed at identifying the knowledge and performance of fundamental and high school's teachers regarding sexuality. Data of this exploratory and descriptive study were obtained though a questionnaire, which was applied to a hundred teachers from the public network school system of the county of Jandira, SP. Results demonstrated that, despite subject relevance for the teachers, they do not have the use of enough knowledge to promote sexual orientation to adolescents, adressing biological issues of sexuality instead of the involving feelings and values. It was concluded that training and education programs about sexuality in adolescence are necessary to this population.